IMPLEMENTASI BALANCED SCORECARD di KOPERASI KARYAWAN dan DOSEN UNIVERSITAS INDRAPRASTA PGRI (UNINDRA) - Akhmad Sefudin; Hendro Prasetyono; Arif Sasmoko (JABE (Journal of Applied Business and Economic), 2014)
This study aims to implement the Balanced Scorecard in Cooperative Employees and University Lecturer Indraprasta PGRI (UNINDRA). The first stage of this study was to measure the performance of Cooperative Employees and University LecturerIndraprasta PGRI the Balanced Scorecard approach continues to find a conclusion whether the Balanced Scorecard can be implemented in a cooperative.The research method used is mixed methodolgy (combined method). Quantitative methods are used to measure the performance of cooperative descriptive and qualitative methods are used to obtain cooperative conclusion and management experts on the implementation of the Balanced Scorecard in the cooperative. Techniques of data collection using a questionnaire (quantitative) and Focus Group Discussion (FGD) for qualitative.The results of performance measurement and Lecturers EmployeesCooperative Unindra the Balanced Scorecard approach as follows: the financial perspective with indicators of current ratio, total debt to asset ratio and net profit margin be weighted 25%, the customer perspective with the indicator member growth, customer satisfaction and student members gain weight 7%, internal business process perspective with the indicators of innovation, the process of operation and after-sales services weights 8.6 and get the perspective of growth and learning with indicators of employee satisfaction, employee retention and productivity of employees earn 11.2% weighting. The total score performance and Lecturers Employees Cooperative Unindra the Balanced Scorecard approach was 51.8%. In conclusion the performance of Cooperative Employees and Lecturer Unindra in 2013 measured by the Balanced Scorecard approach are in a position less amounted to 51.8% can be categorized as a business entity that has an unhealthy level of health (BB). Implementation of BalancedScorecard in the cooperative could not be concluded or not because when progress reports are prepared FGD has not done